Human-machine interface : a case study to investigate the effect of a newly introduced system on the work morale of the people who interact with it - Bradshaw, Jennie (Sheila Jennie) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2003.